Late presenters to HIV care and treatment, identification of associated risk factors in HIV-1 infected Indian population - Chauhan Neeraj K; Vajpayee Madhu; Mojumdar Kamalika; Mendiratta Sanjay (BMC, 2010)
Abstract Background Timely access to antiretroviral therapy is a key to controlling HIV infection. Late diagnosis and presentation to care diminish the benefits of antiretrovirals and increase risk of transmission. We aimed to identify late presenters in patients sent for first CD4 T cell count after HIV diagnosis, for therapy initiation evaluation. Further we aimed at identifying patient factors associated with higher risk of late presentation. Methods Retrospective data collection and analysis was done for 3680 subjects visiting the laboratory for CD4 T cell counts between 2001 and 2007. We segregated the patients on basis of their CD4 T cell counts after first HIV diagnosis. Factors associated with risk of late presentation to CD4 T cell counts after HIV diagnosis were identified using univariate analysis, and the strength of association of individual factor was assessed by calculation of odds ratios. Results Of 3680 subjects, 2936 (83.37%) were defined as late presenters. Late testing varied among age groups, transmission categories, and gender. Males were twice as likely to present late as compared to females. We found significant positive association of heterosexual transmission route (p < 0.001), and older age groups of 45 years and above (p = 0.0004) to late presentation. Female sex, children below 14 years of age and sexual contact with HIV positive spouse were associated with significantly lower risks to presenting late. Intravenous drug users were also associated with lower risks of late presentation, in comparison to heterosexual transmission route. Conclusions The study identifies HIV infected population groups at a higher risk of late presentation to care and treatment. The risk factors identified to be associated with late presentation should be utilised in formulating targeted public health interventions in order to improve early HIV diagnosis.